2017
DOI: 10.1080/21655979.2016.1255383
|View full text |Cite
|
Sign up to set email alerts
|

Developing and characterization of single chain variable fragment (scFv) antibody against frizzled 7 (Fzd7) receptor

Abstract: ABSTACTWnt/b-catenin signaling pathway through Frizzled receptors has been shown to play a key role in both normal development and tumorigenesis. Overexpression of Wnt pathway genes, such as Fzd7 in several malignancies is well-documented. Therefore, targeting of Fzd7 and its ligand inhibits cancer cells proliferation metastasis. In the present study we isolated single chain variable fragments (scFvs) against Fzd7 receptor using phage display method. Semi-synthetic human naive antibody libraries (Tomlinson I C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…Functionally, the scFvs inhibited cell growth by inducing cell apoptosis in a TNBC cell line, MDA-MB-231. The reasons why scFvs antibodies are potential therapeutic agents include small size, high affinity, human origin, and specificity [ 89 , 90 ].…”
Section: Therapeutic Potential Of Fzd Receptorsmentioning
confidence: 99%
“…Functionally, the scFvs inhibited cell growth by inducing cell apoptosis in a TNBC cell line, MDA-MB-231. The reasons why scFvs antibodies are potential therapeutic agents include small size, high affinity, human origin, and specificity [ 89 , 90 ].…”
Section: Therapeutic Potential Of Fzd Receptorsmentioning
confidence: 99%
“…Genetic or pharmacological inhibition of elements of the Wnt/Fzd pathway (Fzd4, LRP-5, Dishevelled, and β-catenin) impairs retinal NV and vascular permeability. [24][25][26] Recent studies have demonstrated that the anti-Fzd7 antibody [27][28][29][30] antagonized Wnt/β-catenin signaling in Fzd7-expressing cancer cells, and suppressed tumor progression and metastasis. 21,22 Dysregulation of Wnt signaling is also associated with ocular diseases with an emphasis on DR. 23 Previously, we have demonstrated that Frizzled-7 (Fzd7) signaling controls post natal vessel formation in the retina, 20 however its role in pathological angiogenesis is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25] Synergistically, Inppl1, Fzd7, and Tgf-b1 were activated as suppressors of cytokine signaling. [26][27][28] Gzmb and Tgf-b1 were confirmed by RT-PCR. A precious signal showed that intravaginal TGF-b can prevent spontaneous abortion in this model despite the recruitment of CD4 þ 8 þ FOXP3 þ cells.…”
Section: Discussionmentioning
confidence: 82%